2021
DOI: 10.3390/ijms22041750
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl-tRNA Synthetases as Valuable Targets for Antimicrobial Drug Discovery

Abstract: Aminoacyl-tRNA synthetases (aaRSs) catalyze the esterification of tRNA with a cognate amino acid and are essential enzymes in all three kingdoms of life. Due to their important role in the translation of the genetic code, aaRSs have been recognized as suitable targets for the development of small molecule anti-infectives. In this review, following a concise discussion of aaRS catalytic and proof-reading activities, the various inhibitory mechanisms of reported natural and synthetic aaRS inhibitors are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 178 publications
(283 reference statements)
0
47
0
Order By: Relevance
“…[ 69 ]. While not a current antimicrobial target, there has been an effort to link mutations in tRNA-ligase to AMR in M. bovis [ 26 ], which could possibly identify targets for using aminoacyl-tRNA synthetase inhibitors as antimicrobials [ 55 , 70 ]. Ledger et al listed 22 tRNA ligases, 13 of which we identified as containing NVs to AMR [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 69 ]. While not a current antimicrobial target, there has been an effort to link mutations in tRNA-ligase to AMR in M. bovis [ 26 ], which could possibly identify targets for using aminoacyl-tRNA synthetase inhibitors as antimicrobials [ 55 , 70 ]. Ledger et al listed 22 tRNA ligases, 13 of which we identified as containing NVs to AMR [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aminoacyl-tRNA synthetases (aaRSs), catalysing the formation of aminoacyl-tRNA, have been explored as targets for the development of antimicrobials [9,[32][33][34][35]. However, HcProRS, located at the C-terminal region of a dual function EPRS, is likewise recognized as a promising target for anti-cancer [12][13][14], anti-fibrosis [11,36] and anti-autoimmune response [37] drug development.…”
Section: Discussionmentioning
confidence: 99%
“…All organisms, including archaea, bacteria, and eukaryotic cells, have ARSs. ARSs are protein synthesis housekeeping enzymes that play an important role in the attachment of tRNAs to their cognate amino acids. , ARSs have been shown in studies to have multiple functions in addition to their catalytic roles. ARSs are thought to be involved in a variety of cellular processes and to contribute to pathophysiological processes. , The nutrient signaling pathways control various signaling cascades that govern cellular energy metabolism as well as cell growth, proliferation, and survival .…”
Section: Discussionmentioning
confidence: 99%